2021
DOI: 10.3390/cancers13153779
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiome as a Potential Target for Therapeutic Manipulation in Pancreatic Cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal cancers and is projected to be the second most common cause of cancer-related death by 2030, with an overall 5-year survival rate between 7% and 9%. Despite recent advances in surgical, chemotherapy, and radiotherapy techniques, the outcome for patients with PDAC remains poor. Poor prognosis is multifactorial, including the likelihood of sub-clinical metastatic disease at presentation, late-stage at presentation, absence of early and reliable di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 160 publications
(226 reference statements)
0
30
0
1
Order By: Relevance
“…Patients with PDAC had an increased phylum Proteobacteria (such as Gammaproteobacteria) and a decreased phylum Firmicutes (such as butyrate-producing bacteria, including Eubacterium rectale, Faecalibacterium prausnitzii , and Roseburia intestinalis ) when compared with healthy controls ( 139 ). Additionally, several recent review articles have underscored the importance of the gut microbiome in the development and progression of PDAC ( 140 – 142 ).…”
Section: The Gut Microbiome and Pancreatic Diseasesmentioning
confidence: 99%
“…Patients with PDAC had an increased phylum Proteobacteria (such as Gammaproteobacteria) and a decreased phylum Firmicutes (such as butyrate-producing bacteria, including Eubacterium rectale, Faecalibacterium prausnitzii , and Roseburia intestinalis ) when compared with healthy controls ( 139 ). Additionally, several recent review articles have underscored the importance of the gut microbiome in the development and progression of PDAC ( 140 – 142 ).…”
Section: The Gut Microbiome and Pancreatic Diseasesmentioning
confidence: 99%
“…The study of the microbiome and its role as a possible prognostic biomarker, along with the potential for its modulation to improve the efficacy and toxicity of existing treatments, has gained significant interest in oncology. In PDAC, it has been suggested that the relatively disappointing results seen with immunotherapy may in some part be attributable to the patient microbiome [96].…”
Section: The Role Of the Microbiome In The Neo-adjuvant Treatment Of Pdacmentioning
confidence: 99%
“…Emerging evidence shows that gut microbiome, an abundant source of TLR ligands, has a critical role in inflammation and treatment resistance in PDAC [68]. A comprehensive study on 1526 PDAC tumors with matched adjacent normal tissues showed that PDAC tumors are dominated by Proteobacteria including the Enterobacteriales and Pseudomonadales species, which are naturally abundant in normal duodenum [69].…”
Section: Toll-like Receptors (Tlrs)mentioning
confidence: 99%